Analysis of Reliability-based Systems of 20kv Distribution Network Disturbance on PT. PLN Rayon Panam - Suripto, Slamet; Putra, Karisma Trinanda; Jusman, Yessi; Aroffi, Muhammad Rusydi Al; Jamaaluddin, Jamaaluddin (Journal of Electrical Technology UMY, 2019)
Electricity needs for each year has increased, this is due to an increase in people's lives. Reliability is an important factor in the operation of distribution system and is an important factor in the continuity of the waiter to the consumer. Several parameters are used as reference to megukur level of reliability of a distribution system that is SAIFI (avarage interuption of frequency index system) is a calculation of the number of failures or disruptions average - average one year, SAIDI (System of interruption Duration Index) index median duration - average system interruption during the year. In this study was also performed calculations eens (Expected Energy Not Supplied) This calculation is done because of disturbance at each feeder there is energy that can not be channeled, it can happen losses. Based on the calculation and analysis that the reliability index is obtained there are some feeder Rayon Panam categorized as not reliable because it has a high SAIFI value not in accordance with the target SPLN No. 68-2 1986 and IEEE std 1366-2003. Energy losses that can not be distributed annually sizeable each feeder. This indicates a feeder located at Panam Rayon considered less reliable, to the need for repairs and maintenance